Influence of Model Refactoring on Code Debt: A Replicated Study - Freire, Emmanuel Sávio Silva; Passos, Amanda Ferraz de O.; Sant’Anna, Cláudio; Spínola, Rodrigo Oliveira; de Mendonça Neto, Manoel G. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Context: The term Technical Debt (TD) is associated with the effect of immature artifacts in the development of software. Although TD may incur in different stages of development, few pieces of research have addressed the relationship between TD in models and its influence on their respective source codes. Goal: To investigate the influence of model refactoring on code debt and vice-versa. Method: A replicated study was conducted considering the refactoring of a Unified Modeling Language (UML) class diagram for the removal of model smells, code issues, and code debt items. Besides, a different round-trip engineering tool was used, other than that employed in the original study. Findings: The findings of the original study were confirmed, but the usage of different engineering tools may influence the quantification of code debt. Conclusion: New replicated studies are necessary to further investigate the influence of model refactoring on code debt, considering other code issues, detection tools and class diagrams.